Implementation of School Operational Assistance Fund During the Covid-19 pandemic (Case Study of SMAN 12 Pekanbaru) - Florencia, Arturis Tua; Yuliani, Febri (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2021)
The purpose of this study was to find out how the process of implementing the use of school operational assistance funds (BOS) at SMAN 12 Pekanbaru, Riau Province, during the Covid-19 pandemic. The coronavirus that is endemic in Indonesia has resulted in limited online and face-to-face learning processes. That changed the allocation of BOS funds to meet school needs during the Covid-19 pandemic. All of that policy to prevent schools from becoming new clusters of the spread of the coronavirus in Indonesia. This research is qualitative with a case study approach. We used primary and secondary data from observations, interviews, and documentation. We analyzed findings to obtain accurate and credible data regarding the implementation of school operational funds during the Covid-19 pandemic. The results showed that the BOS fund policy implementation at SMAN 12 Pekanbaru was still not optimal. The findings support that statement from various main aspects such as communication, resources, disposition, and bureaucratic structure that hinder the success of policy implementationABSTRAKTujuan penelitian ini adalah mengetahui bagaimana proses implementasi penggunaan dana bantuan operasional sekolah (BOS) di SMAN 12 Pekanbaru Provinsi Riau selama pandemi Covid-19. Virus corona yang mewabah di Indonesia mengakibatkan proses pembelajaran dilakukan secara online dan tatap muka terbatas. Alokasi penggunaan dana BOS turut diubah guna memenuhi kebutuhan pembelajaran selama masa pandemi Covid-19. Hal ini dilakukan guna mencegah sekolah menjadi cluster baru penyebaran virus corona di Indonesia. Penelitian ini bersifat kualitatif dengan pendekatan studi kasus. Data yang digunakan ialah data primer dan sekunder yang berasal dari hasil observasi, wawancara, dan dokumentasi yang dianalisis oleh peneliti sehingga mendapatkan data yang akurat dan jelas mengenai implementasi penggunaan dana operasional sekolah di masa pandemi Covid-19. Hasil penelitian menunjukkan bahwa implementasi kebijakan dana BOS di SMAN 12 Pekanbaru masih belum optimal. Temuan ini diukur dari berbagai aspek utama seperti komunikasi, sumber daya, disposisi, dan struktur birokrasi yang menghambat keberhasilan implementasi kebijakan.